NILAI-NILAI KARAKTER DALAM KITAB AKHLAK LIL BANAT JILID 1 KARYA USTADZ UMAR BIN ACHMAD BARADJA - Khullatus Sofiyah; Ahmad Subekti; Kukuh Santosa (VICRATINA, 2020)
In today’s modern era, character education in Indonesia is decreasing. This is the impact of the increasingly widespread technology that can be accessed easily by Everest generation of the nation, resulting in a lack of filters good and bad things that happen. in the end the character values began to lose their true identity. Book titled “Akhlak lil Banat” volume 1  by Ustadz Umar bin Achmad Baradja contains about a girl should do in everday life. This book can be used as a guide for parents and teachers in educating their daughters. In addition , this book has been used in various parts of islamic boarding school in Indonesia as a book that must be studied by each student. This type of research is library research that leads to the thinking of figures, with data analysis methods. The character values contained are responsibility, honest, religious, polite, and curiosity.